2018
DOI: 10.1101/358044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic analysis and identification of factors impacting the diffusion of Foot-and-Mouth disease virus in Africa

Abstract: Foot and mouth disease (FMD) is endemic in sub-Saharan Africa and can lead to important and continuous economic losses for affected countries. Due to the complexity of the disease epidemiology and the lack of data there is a need to use inferential computational approaches to fill the gaps in our understanding of the circulation of FMD virus on this continent. Using a phylogeographic approach we reconstructed the circulation of FMD virus serotypes A, O and SAT2 in Africa and evaluated the influence of potentia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…The fact that the SAT serotypes are mainly maintained within wild buffalo populations does not go against the observation that most of the recent spread of the viruses in Africa seems to be driven by livestock movement [36][37][38] . Moreover, this observation is in concordance with the theory that currently circulating lineage of SAT serotypes re-emerged from a small number of wild buffaloes that survived the African rinderpest epidemic of 1975 10 .…”
Section: Discussionmentioning
confidence: 97%
“…The fact that the SAT serotypes are mainly maintained within wild buffalo populations does not go against the observation that most of the recent spread of the viruses in Africa seems to be driven by livestock movement [36][37][38] . Moreover, this observation is in concordance with the theory that currently circulating lineage of SAT serotypes re-emerged from a small number of wild buffaloes that survived the African rinderpest epidemic of 1975 10 .…”
Section: Discussionmentioning
confidence: 97%
“…It is considered that serotype O originated in the Horn of Africa, with a higher probability of origination in Kenya and Sudan, which act as a link between East and North Africa. Four clades (VP1 nucleotide sequence differences among topotypes disseminated to different parts of Africa) of serotype O FMDV (EA1,2,3,4) were identified using phylogeographic analysis [66]. For their geographic origin, the first clade was composed of viral sequences from Kenya, Tanzania, and Uganda; the second was in Ethiopia; the third was in Sudan; and the fourth was in West and Central African countries.…”
Section: Serotype O Topotypes In the Horn Of Africamentioning
confidence: 99%
“…For their geographic origin, the first clade was composed of viral sequences from Kenya, Tanzania, and Uganda; the second was in Ethiopia; the third was in Sudan; and the fourth was in West and Central African countries. Using evolutionary parameter estimation, it was found that a mean evolutionary rate of 3.41 × 10 −3 nucleotide substitutions per site per year over 58 years was recorded (1958-2016) [55,66]. On the other hand, Munsey from Uganda also estimated the VP1 evolutionary rate to be 4.99 × 10 −3 nucleotide substitutions per site per year [67].…”
Section: Serotype O Topotypes In the Horn Of Africamentioning
confidence: 99%
“…Consequently, there are growing collections of animal virus sequences from around the globe. In this talk, the use of viral sequence data together with phylodynamic methodologies for understanding the transmission patterns in animal populations was discussed, using Avian Influenza (AI), Foot-and-Mouth Disease (FMD) and Porcine Reproductive and Respiratory Syndrome (PRRS) as examples [58,59,60].…”
Section: Sessions and Oral Presentationsmentioning
confidence: 99%
“…Since RNA viruses have fast mutation rates and variable sequences, transmission routes between places and host species can be inferred [59,60]. One approach is to group sequences from individual hosts into discrete locations and/or host species and consider these as discrete traits or subpopulations on time-resolved phylogenetic trees, with the goal to infer which group infected which.…”
Section: Sessions and Oral Presentationsmentioning
confidence: 99%